Arthroscopic Ankle Arthrodesis for Treating Osteoarthritis in a Patient with Kashin-Beck Disease - Iwasa, Kenjiro (Hindawi Publishing Corporation, 2014)
Kashin-Beck disease (KBD) is an endemic degenerative osteoarthritis. Death of cartilage and growth plate is the pathologic feature; therefore, KBD involves skeletal deformity and often results in osteoarthritis. Deficiency of selenium, high humic acid levels in water, and fungi on storage gains are considered the cause of KBD. The most frequently involved joints are ankles, knees, wrists, and elbows and symptoms are pain and limited motions of those joints. The main treatments for KBD are rehabilitation and osteotomy to correct the deformities because preventive treatment has not been established. In this report, we present a case of ankle osteoarthritis due to KBD and first describe arthroscopic ankle arthrodesis for treating osteoarthritis of KBD.